2011
DOI: 10.1016/j.jns.2010.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow is reduced in chronic fatigue syndrome as assessed by arterial spin labeling

Abstract: Background Chronic fatigue syndrome is diagnosed by a set of clinical criteria and therefore is probably heterogeneous. Earlier reports tested the hypothesis that the syndrome had a neurological substrate by doing studies of cerebral blood flow (CBF) but with discrepant results. One possible reason for the discrepancy was that relative CBF was assessed. We found reduced CBF in an earlier study of absolute CBF using xenon-CT. The purpose of this study was to use a second method of assessing CBF and to look with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
88
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(97 citation statements)
references
References 14 publications
7
88
1
1
Order By: Relevance
“…[70][71][72][73][74][75][76][77][78][79][80] A consensus panel of autonomic experts concluded that the literature provided strong evidence for exaggerated venous pooling, diminished red cell mass, reduced plasma volume, disordered sympathetic activity, impaired baroreflex function, and reduced cerebral perfusion. 80,81 The most frequently observed disorders on autonomic testing are postural orthostatic tachycardia syndrome, neurally mediated hypotension, and heart rate variability during head-up tilt testing. Investigators have reported a strong correlation between symptoms of autonomic dysfunction, as assessed by the Composite Autonomic Symptom Scale (COMPASS), and fatigue, as assessed by a validated instrument, the Fatigue Impact Scale.…”
Section: Cognitionmentioning
confidence: 99%
“…[70][71][72][73][74][75][76][77][78][79][80] A consensus panel of autonomic experts concluded that the literature provided strong evidence for exaggerated venous pooling, diminished red cell mass, reduced plasma volume, disordered sympathetic activity, impaired baroreflex function, and reduced cerebral perfusion. 80,81 The most frequently observed disorders on autonomic testing are postural orthostatic tachycardia syndrome, neurally mediated hypotension, and heart rate variability during head-up tilt testing. Investigators have reported a strong correlation between symptoms of autonomic dysfunction, as assessed by the Composite Autonomic Symptom Scale (COMPASS), and fatigue, as assessed by a validated instrument, the Fatigue Impact Scale.…”
Section: Cognitionmentioning
confidence: 99%
“…Billeddiagnostiske og nevropsykologiske tester viser avvikende funn i sentralnervesystemet hos pasienter med CFS/ME (37)(38)(39)(40)(41)(42)(43) . «Sentral sensitisering» (utvikling av hypersensitivitet for ulike stimuli i sentralnervesystemet), kan vaere en mekanisme ved CFS/ME (44)(45)(46) .…”
Section: Utløsende Faktorerunclassified
“…Cerebral blood flow is decreased in most, but not all, ME/CFS patients [30], and the cortical blood flow appears to be most affected [31]. The reduction of cerebral blood flow led the Authors to hypothesize that low global cerebral flow was associated with abnormal brain neuroimaging results and objective evidence of brain dysfunction in the form of reduced cognitive testing scores [30].…”
Section: Cadmium and Angiogenesis In Me/cfsmentioning
confidence: 99%
“…Cerebral cortex blood flow could be measured with functional magnetic resonance imaging as in [30] and/or also with the transcranial sonography technique described above. In fact, with the type of setting described and using Doppler technique, we could also observe arterial vascularisation of the meninges and of cortex of the temporal lobe and pulsating arteries of about one mm diameter could be easily visualized (Fig.…”
Section: Cadmium and Angiogenesis In Me/cfsmentioning
confidence: 99%
See 1 more Smart Citation